A green method for the synthesis of Copper Nanoparticles using L-ascorbic acid - Umer,Asim (2014)
Chemical Reduction technique was employed to prepared highly stable and dispersed Copper nanoparticles using L-Ascorbic Acid (Vitamin C) as reducing as well as capping agent. In this technique, cupric chloride was used as precursor. The effects of different molar ratios of L-Ascorbic Acid on the concentration and size of copper nanoparticles were studied. The Copper nanoparticles were characterized by X-Ray Diffraction, Atomic Absorption Spectrometry, and Fourier Transform Infrared Spectrometry. The results show that with the increase in the molar ratio of L-ascorbic acid the concentration of Copper nanoparticles were also increased. The average particles size of copper nanoparticle was found in the range of 50-60 nm. The product was kept in ambient conditions for three month but no sedimentation or separation was observed. The use of ascorbic acid makes the process a non-toxic, cost effective and environmental friendly green method.